165 Changes in cause-specific mortality among older adults in the United States, 1999–2020. (20th November 2022) - Lee, Robin; Kakara, Ramakrishna; Eckstrom, Elizabeth; Qualters, Judith
Abstract : Background: Injuries are a leading cause of disability and death among older adults across the globe. In 2020, unintentional injuries were the 8th leading cause of death among U.S. older adults (ages 65+). These deaths are primary attributed to falls (58%) and transportation-related deaths (13%). Aim: Assess the burden injuries have on the aging U.S. population and resources to prevent injury-related deaths. Methods: The leading causes of death between 1999–2020 and sub-categories for unintentional injuries were extracted from the U.S. National Vital Statistics System. Age-adjusted cause specific death rates and average annual percent change (AAPC) estimates were calculated. Results: The rates of seven out of the ten causes decreased significantly, while the rates of deaths due to Alzheimer's disease (AAPC 3.0%; 95%CI:1.5 to 4.5) and unintentional injuries (AAPC 1.2%; 95%CI:1.0 to 1.4) significantly increased. About half of the 953, 643 unintentional injury deaths were due to falls. Fall death rates increased 136% from 1999 to 2020, at an average 4.1% (95%CI: 3.9 to 4.3) per year. Outcomes: The observed changes in cause-specific mortality suggests the need for more awareness about injuries and prevention as we age. Still Going Strong (www.cdc.gov/stillgoingstrong) is a new U.S. awareness campaign to educate older adults about steps they can take to avoid injuries as they age. Steps include performing exercises to improve strength and mobility, planning for future mobility (https://bit.ly/3HxrlT6), and speaking with a healthcare provider about reducing medications that can increase the risk for injury. Learning objectives: Learn how to prevent injures as we age.